Utilizing an Electronic Health Record System to Improve Vaccination Coverage in Children - Au, L.; Oster, A.; Yeh, G. H.; Magno, J.; Paek, H. M. (Applied Clinical Informatics, 2010)
Background: Electronic Health Records (EHR) are widely believed to improve quality of care and effectiveness of service delivery. Use of EHR to improve childhood immunization rates has not been fully explored in an ambulatory setting.Objective: To describe a pediatric practice’s use of Electronic Health Records (EHR) in improving childhood immunization.Methods: A multi-faceted EHR-based quality improvement initiative used electronic templates with pre-loaded immunization records, automatic diagnosis coding, and EHR alerts of missing or delayed vaccinations. An electronic patient tracking system was created to identify patients with missing vaccines. Barcode scanning technology was introduced to aid speed and accuracy of documentation of administered vaccines. Electronic reporting to a local health department immunization registry facilitated ordering of vaccines.Results: Immunization completion rates captured in monthly patient reports showed a rise in the percentage of children receiving the recommended series of vaccination (65% to 76%) (p<0.000). Bar-code technology reduced the time of immunization documentation (86 seconds to 26 seconds) (p<0.000). Use of barcode scanning showed increased accuracy of documentation of vaccine lot numbers (from 95% to 100%) (p<0.000).Conclusion: EHR-based quality improvement interventions were successfully implemented at a community health center. EHR systems have versatility in their ability to track patients in need of vaccines, identify patients who are delayed, facilitate ordering and coding of multiple vaccines and promote interdisciplinary communication among personnel involved in the vaccination process. EHR systems can be used to improve childhood vaccination rates.
Keywords: Electronic Health Records; pediatrics; childhood vaccinations; immunization registry